NEP 2020 and Inclusive Education: Addressing Equity Challenges in Indian Education - K SUDHAKAR (AG Volumes, 2025)
At the core of our educational system is the National Education Policy -2020. This visionary is driving significant progress towards equality and equity in our educational system. The core idea of NEP-2020 is inclusion in mainstream education. Every policy’s actual implementation in the field is always accompanied with a question mark. The use of remedies should be limited, and it is implied that all stakeholders, including parents and teachers, should intercept the difficulties in order to improve the effectiveness of all treatments. Through NEP 2020, this research reviewed the issues of equity and inclusive education in Indian schools. Inadequate infrastructure, restricted possibilities, low engagement, and the need for a more compassionate educational system were identified as the main issues. Notwithstanding the significant strides achieved by NEP 2020 in advancing inclusive teaching practices and digital technologies, enduring problems including inadequate infrastructure, poor teacher preparation, and uneven access to resources—especially for underserved communities—linger.